Shells of intertidal mudflat snails: a promising biomonitoring materials of nickel pollution - Yap, Chee Kong; Tan, Wen Siang; Ismail, Mohamad Saupi; Ariffin, Noorhaidah; Cheng, Wan Hee; Bintal, Amin; Zakaly, Hesham M. H.; Peng, Shih Hao Tony; Yap, Chee Wah; Edward, Franklin Berandah (Universal WISER, 2022)
Monitoring the level of metal pollution in a water body, especially in polluted areas, is crucial. Gastropod shells have been used as a biomonitor for metal pollution. The goal of this study was to evaluate the utilisation of the mudflat snails, Telescopium telescopium shells, as biomonitoring materials for nickel (Ni) pollution in the intertidal area. The snails and their habitat surface sediments were sampled from 17 sites in Peninsular Malaysia. Up to 21 individuals from each site were sampled and dissected. In addition to the shells, six parts of the soft tissues (cephalic tentacle, foot, gill, muscle, mantle, and remaining soft tissues) were analysed for Ni. The snail shell was found to be a potential biomonitoring material for Ni pollution based on four positive points: (i) higher value of shell/soft tissue ratios (> 1.00); (ii) categorisation as a ‘microconcentrator’ based on bioaccumulation factor; (iii) significant correlation coefficients (at least P < 0.05) and significant influential total Ni levels in the sediments to the shell Ni; and (iv) higher precision of Ni in the shells based on the lowest value of the coefficient of variation of Ni. The described results indicated that the shell of T. telescopium would be suitable for assessing Ni pollution in the intertidal areas.